Double Vulnerabilities of Unregistered Wife After The New Kuhp: An Analysis of The Cohabitation Article As a Threat of Structural Victimization - Rizky Wibowo; Nahar Surur (Faculty of Law, Muhammadiyah University of Surabaya, 2025)
Article 412 of Law No. 1 of 2023 concerning the Criminal Code (the Cohabitation Article) is often promoted as a guardian of public morality. However, for those practicing nikah siri (unregistered marriage), this article creates a new dimension of threat that did not previously exist. This study aims to dissect how the cohabitation article in the New Criminal Code potentially serves as an instrument of structural victimization for unregistered wives. This study employs a socio-legal research method with a criminological-victimology and critical legal theory approach. The study finds that unregistered wives face